Beiträge zur Theaterwissenschaft Südosteuropas und des mediterranen Raums 1. Band - Puchner, Walter
This is a volume of 12 studies on specific topics of theatre and drama history in the Balkans and the Eastern Mediterranean. The scientific interest in the culture of this area during the unification process of Europe is increasing. Five of these studies are of comparative nature, seven focus on Greece and its European connections in the field of theatre and drama. The first part includes the following studies: "Typological structures of development in the theatre history of Southeastern Europe", "Comparative contributions to the traditional puppet theatre in the Balkan pensinsula", "Black-eye Karagöz and the history of shadow theatre in the Balkans under the Turkish rule", "The repraesentatio figurata of the Presentation of the Virgin in the Temple by Philippe des Mézières (Avignon 1372) and its supposed Cypriotic origin", and "Skenderbey in European and Balkan drama".The second part consists of the following studies: "The descensus ad inferos as nuclear scene of an inexistent Orthodox resurrection play", "Structures of reception of Early Modern Greek drama", "Religious baroque theatre during the processions of Corpus Christi on the Cyclades in the 17th century", "Religious festivals of the Baroque era on the islands of the Archipelagus under the Turkish rule (Capucins, Chios 1673)", "Greek editions in Vienna from Gluck to Kotzebue. The theatre life of the Danubian capital in Greek translations 1780-1820", "Literature and theatre in Greece 1728-1888", and "Constantin Christomanos and the theatre of fin de siècle in Austria and Greece".Comparative studies in South Eastern Europe and the Eastern Mediterranean, especially in theatre and drama history, are very rare. Some of these studies are ground-breaking in specific subjects. Exhaustive registers will bring these studies together thematically, studies which in sum, together with the ones of the second volume, will give an idea of a future handbook on Southeatersn Europe theatre and drama from the Midde Ages up to the 20th century.